Influence Factors of Emergency Medical Services (EMS) Prehospital Time Interval Variety: A Systematic Review - Anggun Setyarini; Heni Dwi Windarwati (Jurnal Ners, 2020)
Introduction: Prehospital time interval was one of important indicators of EMS performance. It consisting of total prehospital time (TPT), response time (RT), on-scene time (OST) and transport time (TT) in the world is very diverse. Many factors were able to affect the duration of prehospital time. The purpose of this systematic review was to identify internal and external EMS factors that affect prehospital time which was useful as a predictor of the prehospital time interval variety.Methods: This study was conducted with a systematic method by reviewing the literature obtained from four electronic databases namely ProQuest, PubMed, ScienceDirect, and Google Schoolar. Seven keywords were used to get some of relevance literatures. Using PRISMA flow diagram, the literatures were screened by three inclusion criteria: original research article, published in the 2007-2018 timeframe, discusses EMS prehospital time interval and the factors that influence it.Results: Seventy-five literature were obtained, of which 14 articles met the requirements for analysis. Factors influencing prehospital time variations can be classified as two. First, internal factors which include: facilities and infrastructure, human resources, and service protocols. Second, external factors which include: natural and non-natural environment, and the patient's clinical condition.Conclusion: Investigation at prehospital time intervals and influential factors is useful in developing evidence-informed in assessing EMS performance and correcting the obstacles found. This review also identifies the gaps in the existing literature to inform future research efforts.